Deficiency of the serine peptidase Kallikrein 6 does not affect the levels and the pathological accumulation of a‐synuclein in mouse brain. Issue 6 (19th October 2020) - Samantha Sykioti, Vasia; Karampetsou, Mantia; Chalatsa, Ioanna; Polissidis, Alexia; Michael, Iacovos P; Pagaki‐Skaliora, Marina; Nagy, Andras; Emmanouilidou, Evangelia; Sotiropoulou, Georgia; Vekrelli s, Kostas
Abstract: Several lines of evidence indicate that the propagation of misfolded α‐synuclein (α‐syn) plays a central role in the progression and manifestation of Parkinson's disease. Pathogenic α‐syn species can be present in the extracellular space. Thus, the identification and modulation of the key enzymes implicated in extracellular α‐syn turnover becomes vital. Kallikrein peptidase 6 has been identified as one of the major α‐syn degrading enzymes and has been implicated in the clearance of extracellular α‐syn. However, the physiological role of this enzyme in regulating α‐syn, in vivo, still remains elusive. Here, by utilizing Klk6 knock‐out ( Klk6 −/− ) mice as our experimental model, we provide insight into the physiologic relevance of endogenous KLK6 expression on α‐syn processing. Behavioral phenotyping showed that Klk6 −/− mice display no gross behavioral abnormalities. Further in vivo characterization of this mouse model, in the context of α‐syn accumulation, showed that KLK6 deletion had no impact on the protein levels of intracellular or extracellular α‐syn. Upon in vivo administration of α‐syn pre‐formed fibrils (PFF), α‐syn pathologic accumulations were evident both in the brains of Klk6 −/− mice and wt mice without significant differences. Intrastriatal delivery of active KLK6, did not affect secreted α‐syn levels observed in the A53T α‐syn over‐expressing mice. These findings suggest that in the in vivo setting of PFF pathology induction, KLK6 alone is not able to modulate pathology transmission. Our study raises implications for the use of recombinant α‐syn fibrils in α‐syn turnover studies. Abstract : KLK6 is a secreted serine protease that has been reported to cleave α‐synuclein conformers in vitro and in vivo. Using a klk −/− mouse model, we have found that KLK6 absence does not affect the intracellular and extracellular levels of α‐synuclein, does not induce accumulation of pathological α‐synuclein nor causes cognitive or motor deficits. Our data suggest that KLK6‐independent mechanisms could operate in this in vivo setting to cleave α‐synuclein thereby regulating its levels extracellularly.